Effects of an Endophytic Fungus Umbelopsis dimorpha on the Secondary Metabolites of Host–Plant Kadsura angustifolia - Qin, Dan; Wang, Ling; Han, Meijun; Wang, Junqi; Song, Hongchuan; Yan, Xiao; Duan, Xiaoxiang; Dong, Jinyan (Frontiers in Microbiology, 2018)
Fungal endophytes live widely inside plant tissues and some have been revealed to provide benefits to their host and ecological environment. Considering the fact that endophytes are engaged in remarkably stable long-term interactions with the host for their whole life cycle, it’s conceivable that both partners have substantial influence on each other’s metabolic processes. Here, we investigated the fermented products of an endophytic fungus Umbelopsis dimorpha SWUKD3.1410 grown on host–plant Kadsura angustifolia and wheat bran, respectively, to assess the impact of SWUKD3.1410 on the secondary metabolites of K. angustifolia. Twenty compounds (1–20) were isolated and identified as 11 schitriterpenoids (1–9, 17–18), two lignans (10, 20), two sesquiterpenoids (11–12), one trinorsesquiterpenoid (13), one monoterpene (14), one sterol (19), and two simple aromatic compounds (15–16) by the extensive 1D-, 2D-NMR and HR-ESI-MS data analysis. Except for nigranoic acid (1), compounds 2–19 have been firstly found from K. angustifolia. Of them, metabolites 2, 11, and 14 were identified to be new. Obtained results indicated that U. dimorpha SWUKD3.1410 could not only produce the same/similar components as its host does, and modify the host–plant components, but also enhance the production of these highly oxygenated schitriterpenoids/schinortriterpenoids in plants. This study suggested an interesting prospective for setting up alternative processing techniques to improve the quality of crude drugs derived from K. angustifolia and increase their values.